ASAS PERTANGGUNGJAWABAN TERHADAP KORPORASI YANG MELAKUKAN TINDAK PIDANA PERBANKAN - Nurul Sasmita (Badamai Law Journal, 2016)
The aims of this thesis is (1) to investigate andexplain the positions of corporations in conducting banking criminalacts, and (2) also to identify and explain the criminal responsibility ofbank as the perpetrator in banking criminal acts. This research isnormative, conceptual approach and the approach of legislationregarding responsibility principles of the corporation for banking criminalacts.Corporations have chances in committing a crime, especially bankingcriminal acts just by making a corporation recognized as a subject ofexistence apart from human beings, so that in practice there is a criminal offense committed by the corporation. The corporation takespart in the occurrence of a crime. In practice, the determination of acriminal offenseconducted by the corporation is known through two things: first, the works of the committee: they should be constructed as theyuse the principles of the liability of corporation’s criminal actions. Principally, stakeholders and officials or employees of a corporationhave the responsibility for its owncorporate actions; second, errors in the corporation,as long as it is in the science of criminal law, the overview of criminals is still oftenassociated with physical actions performed by the manufacturers(fysieke dader) but this can be overcome by the study of  "functionalactors" (functioneledader). We can prove that the action of committeeor employees of the corporation in the society act traffic concerned,the acts of the corporationerrors in the forms (dolus or culpa) must be regarded ascorporate faults.Towards the corporations that make banking criminal acts we canhave their responsibility with the principles of strict liability. Onthe principle of strict liability, it is known that the responsibility ison them even if they do not have the required mens rea. The substanceof this principle is that the perpetrator has been punished if theperpetrator may have provable conduct prohibited by the criminalprovision (actus reus) withoutsee the inner attitude. In this conception, the corporation is consideredhaving responsibility forphysical acts performed by management. A corporation convicted in principles isintended to develop a sense of justice in the corporation who commitsbanking criminal acts as stated in Article 46 paragraph (2), sothat if a corporation committed criminal acts, we can also have theresponsibility of the corporation. Keywords:Banking Criminal Acts, Corporation, ResponsibilityMenurut peraturan perundang-udangan, korporasi sebagai subyek hukum dapat dikenakan pidana sebagaimana manusia melakuka tindak pidana. Pada praktiknya, penentuan tindak pidana yang dilakukan oleh korporasi diketahui melalui dua hal, yaitu pertama tentang perbuatan pengurus yang harus dikonstruksikan sebagai perbuatan korporasimaka digunakanlah asas pertanggungjawaban pidana. Pada asas tersebut stakeholder maupun pengurus atau pegawai suatu korporasi, bertanggungjawab terhadap perbuatan korporasi itu sendiri. dan kedua tentang kesalahan pada korporasi, memang selama ini dalam ilmu hukum pidana gambaran tentang pelaku tindak pidana masih sering dikaitkan dengan perbuatan yang secara fisik dilakukan oleh pembuat (fysieke dader) namun hal ini dapat diatasi dengan ajaran “pelaku fungsional” (functionele dader). Kita dapat membuktikan bahwa perbuatan pengurus atau pegawai korporasi itu dalam lalu lintas bermasyarakat berlaku sebagai perbuatan korporasi yang bersangkutan maka kesalahan dalam bentuk (dolus atau culpa) mereka harus dianggap sebagai kesalahan korporasi. Terhadap korporasi yang melakukan tindak pidana perbankan dapat dimintai pertanggungjawaban pidana dengan menggunakan asas strict liability.Pada asas strict liability diketahui bahwa pembebanan tanggung jawab pidana kepada pelakunya sekalipun pelakunya tidak memiliki mens rea yang dipersyaratkan. Adapun substansi dari asas ini adalah pelaku sudah dapat dijatuhi pidana apabila pelaku telah dapat dibuktikan melakukan perbuatan yang dilarang oleh ketentuan pidana (actus reus) tanpa melihat sikap batinnya. Dalam konsepsi ini, korporasi dianggap bertanggung jawab atas perbuatan yang secara fisik dilakukan oleh pengurus (direksi dan komisaris). Dipidananya korporasi pada asas ini dimaksudkan dapat menimbulkan rasa keadilan pada korporasi yang melakukan tindak pidana perbankan, sehingga apabila korporasi melakukan tindak pidana maka korporasi juga dapat dimintai pertanggungjawaban.Kata kunci: Korporasi, Pertanggungjawaban, Tindak Pidana Perbankan